Application of Attendance Monitoring System Using RFID (Radio Frequency Identification) and Interface - Muhammad Syahputra Novelan (Institute of Computer Science (IOCS), 2020)
The design of the attendance monitoring system prototype is made using the RFID (Radio Frequency Identification) sensor. RFID equipped with a reader and tag. Reader used as a medium for reading attendance information and tags used as ID cards. The tools to be made will be integrated with a database so that the attendance system can be monitored using a desktop application. The database will be designed using Mysql and Xampp. The GUI (Graphic User Interface) which will be used as a media interface is designed using the Visual Basic application so that data that has been integrated with the database can be easily monitored using a desktop application. The system that is integrated with the database allows data to be automatically stored in the database, making it easier for admin to recap their attendance.